Aging effects on the mongolian gerbil female prostate (Skene's paraurethral glands): Structural, ultrastructural, quantitative, and hormonal evaluations - Custodio, Ana Maria G. (2008)
Different from the classic view, the prostate is not a gland exclusive to the male, also being an organ of the female genital system presenting morphofunctional similarity between human and rodent. Thus structural, ultrastructural, morphometric-stereological features of the female prostate (Skene's paraurethral gland) and steroid serological levels were evaluated during young, adult, and senile ages in the Mongolian gerbil. The morphofunctional precocity of the female gland in comparison with the male gland occurring in young gland is probably associated with the female circulating steroid levels. The hormonal imbalance in senesce coincides with its susceptibility to histopathological lesions, such as epithelial hypertrophy, metaplasia, and intraepithelial neoplasia. Differently than that of males, the aging degeneration of the female gland involves the accumulation of lipofuscin granules. However, the alterations in senile prostate did not damage its functionality. These analyses reinforce the use of this experimental model for the comprehension of glandular morphofunctional aspects with special attention to senescence. Thus, the appreciation of this organ becomes relevant to avoid future discomfort to women's health.